Central airway obstruction tumour debulking using rigid bronchoscopy and cryotherapy: a case report - Chew, Wai Heng; Marwan, Abdul Aziz; Daut, Ummi Nadira; Ismail, Rosmadi; Nasaruddin, Mona Zaria; Abdul Rahman, Jamalul Azizi (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Sarcomas usually frequented in the head and neck region of young adults. Trachea is a rare site, and due to scarce clinical data, its clinical outcome is unclear. We reported a case of 60-year old patient presented with progressive worsening shortness of breath, cough, and progressive worsening dysphagia. Computer tomography scan revealed extensive 2 lobulated soft tissue lesions within and surrounding the trachea at the T4 level. Rigid bronchoscopy with mass cryo-debulking was performed and ultimately synovial sarcoma was diagnosed. Shortness of breath was completely relieved post-procedure.